2017
DOI: 10.1016/j.jval.2017.08.685
|View full text |Cite
|
Sign up to set email alerts
|

Off-Label Drug Use In Hospitalized Children: A Prospective Observational Study At Gondar University Referral Hospital, Northwestern Ethiopia

Abstract: A519 days; In KPI5 58% of patients received adjuvant chemotherapy within 60 days after surgery; In KPI6 57% of patients performed radiotherapy within 90 days after surgery (who did not receive adjuvant chemotherapy) and 69% within 180 days after surgery (who received adjuvant chemotherapy); In KPI7 74% of the patients with tumor stage I and II performed one diagnostic examinations within 365 months after surgery. ConClusions: This study sustains the replicability of E.Pic.A. in different realities, the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
6
1
1
Order By: Relevance
“…Co-amoxiclav, ceftriaxone, and ciprofloxacin were frequently used as an off-label/unlicensed drug. This finding was different when compared to the other study conducted in Ethiopia which reported ceftriaxone, cloxacillin, and gentamicin as the commonly used offlabel antibiotic used [29]. Ciprofloxacin was frequently used as the off-label drug among neonates.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Co-amoxiclav, ceftriaxone, and ciprofloxacin were frequently used as an off-label/unlicensed drug. This finding was different when compared to the other study conducted in Ethiopia which reported ceftriaxone, cloxacillin, and gentamicin as the commonly used offlabel antibiotic used [29]. Ciprofloxacin was frequently used as the off-label drug among neonates.…”
Section: Discussioncontrasting
confidence: 69%
“…Most of the drugs prescribed to pediatrics are utilized outside the specifications of licensed drug which include the indication, dose, route of administration, and age groups of patients [1][2][3][4]. Use of off-label/unlicensed drugs in the pediatric population is widespread that mainly occurs in medical and surgical wards as well as in intensive care units (ICUs) [2,5]. Use of off-label drugs gives rise to inconsiderable adverse drug event that requires hospitalization and additional therapies [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…10 Whereas the highest percentage (31.7% and 78.1%) was reported from Brazil and Ethiopia. 11,12 Although the majority of our practitioners irrespective of their status reported that 10% of their prescriptions to the children in the previous year were offlabel, 23% of our pediatricians reported that more than 26% of their prescriptions in the previous year were off-label in nature. A similar trend was observed in other studies within the country, of which 29.7% (173/583) and 12.9% (75/583) were classified as off-label and unlicensed drugs respectively.…”
Section: Discussionmentioning
confidence: 91%
“…It was observed that children at an age of 2-11 years old were routinely prescribed with off-label drugs (43%), which are in confirmation with previous studies from Ethiopia and Germany. 12,15 Irrespective of the age group of the children, pediatricians use off-label medications broadly, while specialists and general practitioners have limited the number of their off-label prescription in neonates and preterm (5%). The FDA policy undeniably declares the use of a pharmaceutical product once approved, for indications, dosages, routes, or age groups other than the approved on the label.…”
Section: Discussionmentioning
confidence: 99%
“…Sebagian besar anak-anak sering menderita infeksi saluran pernapasan akut (ISPA) hal ini karena sistem kekebalan tubuh anak belum berkembang sempurna, respon imunitas yang masih berkembang dan dilihat dari faktor lingkungan berupa gizi dan polusi udara dimana dalam kelompok usia yang tergolong masih anak-anak lebih bayak beraktivitas diluar rumah, lebih suka bermain ditempat kotor dan berdebu sehingga lebih rentan terhadap penyakit [5]. Demam tifoid da dehidrasi (kekurangan cairan) juga sering terjadi pada anak-anak [6], [7].…”
Section: Hasil Dan Pembahasanunclassified